Case Report: Complete Remission of a Patient With Metastatic Gastric Cancer Treated With Nivolumab Combined With Chemotherapy After Palliative Surgery - Dai, Peilin; Rao, Xi; Zhang, Xi; Qiu, Enming; Wu, Gang; Lin, Yu; Li, Sitong; Li, Zhou; Cai, Zhai; Han, Shuai (Frontiers in Immunology, 2022)
Metastatic advanced gastric cancer whose treatment strategies are extremely limited, has a poor prognosis. Complete remission is a rare phenomenon. Patients usually lose the opportunity of therapeutic surgery because the lesions fail to be completely removed, although it can greatly prolong the survival time. At the same time, palliative surgery usually means bad outcomes. In recent years, immune checkpoint inhibitor nivolumab has shown significant efficacy in the treatment of advanced gastric cancer. However, its low response rate and high incidence of immune related adverse events make its applicable conditions and optimal withdrawal time still controversial in academia. Herein, we introduce a 66 year old male patient with advanced gastric cancer with multiple liver metastases who underwent laparoscopic total gastrectomy for acute gastric bleeding. The patient received 8 cycles of S-1 plus oxaliplatin (SOX) and switched to 8 cycles of SOX plus nivolumab combined regimen in a stable state, and then achieved complete remission. There was no recurrence for 32 months after operation. This is the first reported case of gastric cancer with multiple liver metastases with long-term complete remission with nivolumab treatment after palliative surgery. The potential mechanism of complete remission was discussed through clinical, genomic and immune characteristics. The characteristics of the history of psoriasis and programmed death ligand 1 (PD-L1) positive, and the interaction of TP53 mutation and HER-2 (-) gene may be associated with complete remission.